Preparation method of high-temperature titanium alloy metallographic specimen
By optimizing the composition of the polishing liquid and the treatment of the corrosion liquid, the problems of low preparation efficiency of high-temperature titanium alloy metallographic samples and difficult to show metallographic structure are solved, and the effect of efficient preparation and accurate analysis is achieved.
Patent Information
- Application Number
- CN202411766951.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
AI Technical Summary
The preparation efficiency of high-temperature titanium alloy metallographic samples in the prior art is low, surface scratches are difficult to remove, metallographic structure is difficult to corrode, affecting the analysis of material structure performance.
By controlling the composition of the polishing liquid used in coarse polishing and fine polishing, the scratches on the surface of the sample are quickly removed, and by controlling the heating temperature and erosion time of the corrosion liquid, the metal phase structure is clearly and quickly corroded.
The preparation efficiency of high-temperature titanium alloy metallographic samples is improved, and the metallographic structure is clearly displayed, ensuring accurate analysis and judgment of the overall structure of the material.
Smart Images

Figure CN119555459A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallographic preparation, and in particular relates to a method for preparing a high-temperature titanium alloy metallographic sample. Background Art
[0002] Titanium alloys have become advanced materials widely used in chemical industry and other related fields due to their high specific strength, excellent corrosion resistance and thermal stability. High-temperature titanium alloys have excellent high-temperature strength, high creep resistance, high heat resistance, thermal strength, thermal stability and other advantages, and have been widely used.
[0003] Ti650 alloy is a near-α-type high-temperature titanium alloy of Ti-Al-Sn-Zr-Mo-Si-Nb-Ta-C series. It is an alloy independently developed by my country for use in a high-temperature environment of 650℃. The alloy uses multi-element alloying elements for solid solution strengthening. In order to make the product obtain fine grains, uniform structure, and the best matching of strength-plasticity and meet the actual use needs, the Ti650 alloy material after hot processing needs to be subjected to solid solution aging heat treatment, in which water cooling is performed after solid solution treatment, and then aging treatment is performed. Since the strength of the material is improved and the hardness is increased after solid solution aging treatment, it is difficult to eliminate the scratches on the surface of the metallographic sample, and the sample polishing time is long and the efficiency is low. At the same time, due to the fast cooling speed of water cooling, the metallographic structure obtained by the conventional metallographic sample preparation method is not easy to be corroded and revealed, which affects the analysis and judgment of the overall structure of the material. In view of this, it is urgently necessary to provide a high-temperature titanium alloy metallographic sample preparation method, which can improve the efficiency of metallographic sample preparation and make the obtained metallographic structure phase distribution clear, so as to further analyze the material structure and performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing metallographic samples of high-temperature titanium alloys in view of the deficiencies of the above-mentioned prior art. The method controls the composition of the polishing liquid used for rough polishing and fine polishing, quickly removes scratches on the sample surface, greatly improves the efficiency of preparing metallographic samples of high-temperature titanium alloys, and combines the control of the heating temperature and erosion time of the corrosive liquid used for corrosion, so that the metallographic structure of the metallographic sample of the high-temperature titanium alloy is clearly and quickly corroded and revealed, ensuring the accuracy of the analysis and judgment of the overall structure of the high-temperature titanium alloy material, and solving the problems of long polishing time, low preparation efficiency and difficulty in corroding and revealing the metallographic structure in the prior art.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-temperature titanium alloy metallographic sample, characterized in that the method comprises the following steps:
[0006] Step 1: Grind the high-temperature titanium alloy sample using 150#, 500#, 1000#, and 2000# water-abrasive sandpaper in sequence, grinding each level of sandpaper for 3min to 5min, and rotate the high-temperature titanium alloy sample 90° each time the next level of sandpaper is replaced;
[0007] Step 2, rough polishing the high-temperature titanium alloy sample ground in step 1 to a slightly bright state; the polishing liquid used for the rough polishing is a CrO3 aqueous solution containing AlO powder, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 1 to 6:100, the ratio of the mass of AlO powder to the volume of the CrO3 aqueous solution is 1 to 10:100, the unit of mass is g, and the unit of volume is mL;
[0008] Step 3, fine-polishing the high-temperature titanium alloy sample after rough polishing in step 2 until it is mirror-bright and scratch-free; the polishing liquid used for the fine polishing is a CrO3 aqueous solution containing Cr2O3, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 1 to 6:100, and the ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution is 1 to 8:100, the unit of mass is g, and the unit of volume is mL;
[0009] Step 4: Place the high-temperature titanium alloy sample finely polished in step 3 in an ultrasonic cleaning apparatus for oscillation cleaning for 3 to 5 minutes, and blow dry with a hair dryer;
[0010] Step 5, placing the high-temperature titanium alloy sample dried in step 4 into a corrosive solution for corrosion, then rinse it with water, spray it with ethanol solution and use a hair dryer to dry it to obtain a high-temperature titanium alloy metallographic specimen, and place it under an optical microscope for metallographic structure observation; the raw materials for the preparation of the corrosive solution include HF solution with a mass concentration of more than 40.0%, HNO3 solution with a mass concentration of 65.0% to 68.0%, and CH3CH(OH)COOH solution with a mass concentration of 85.0% to 90.0%, and the volume ratio of HF solution: HNO3 solution: CH3CH(OH)COOH solution is 1:3:7 to 10. First, heat the corrosive solution in a water bath to 40°C to 60°C, and then put the dried high-temperature titanium alloy sample into it for etching for 10s to 30s.
[0011] The above-mentioned method for preparing a metallographic sample of a high-temperature titanium alloy is characterized in that a coarse canvas is used for the rough polishing in step 2, and the CrO3 aqueous solution is a mixture of CrO3 with a mass purity of not less than 99.0% and water. The present invention uses a strong and wear-resistant coarse canvas and an oxidizing CrO3 aqueous solution for rough polishing, which can effectively remove the coarse scratches on the surface of the high-temperature titanium alloy sample and make its surface reach a slightly bright state.
[0012] The above-mentioned method for preparing a high-temperature titanium alloy metallographic sample is characterized in that the AlO powder in step 2 is an aluminum oxide polishing micropowder with a particle size of 1 μm to 2.5 μm. The AlO powder has high mechanical strength, wear resistance, and stability. The polishing liquid containing the AlO powder added to the CrO3 aqueous solution can quickly remove the coarse scratches on the surface of the high-temperature titanium alloy sample.
[0013] The above-mentioned method for preparing a metallographic sample of a high-temperature titanium alloy is characterized in that the mass ratio of CrO3 in the CrO3 aqueous solution in step 2 to the volume ratio of water is 2 to 4:100, the AlO powder is an aluminum oxide polishing micropowder with a particle size of 1 μm to 1.5 μm, the mass ratio of the AlO powder to the volume ratio of the CrO3 aqueous solution is 3 to 6:100, the unit of mass is g, and the unit of volume is mL. The polishing liquid using the AlO powder and CrO3 aqueous solution of this specific composition can effectively and quickly remove the coarse scratches on the surface of the high-temperature titanium alloy sample, making its surface reach a slightly bright state.
[0014] The above-mentioned method for preparing a metallographic sample of a high-temperature titanium alloy is characterized in that fine silk cloth is used for fine polishing in step 3, and the CrO3 aqueous solution is a mixture of CrO3 with a mass purity of not less than 99.0% and water. The present invention uses soft, smooth and fine fine silk cloth and a CrO3 aqueous solution with good stability and wear resistance for fine polishing, which can effectively remove fine scratches on the surface of the high-temperature titanium alloy sample.
[0015] The above-mentioned method for preparing a high-temperature titanium alloy metallographic sample is characterized in that the ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution in step 3 is 2 to 5:100, the unit of mass is g, and the unit of volume is mL. The polishing liquid of the Cr2O3 and CrO3 aqueous solution of the specific composition can effectively and quickly remove fine scratches on the surface of the high-temperature titanium alloy sample, making its surface reach a mirror-bright, scratch-free state.
[0016] The above-mentioned method for preparing a high-temperature titanium alloy metallographic sample is characterized in that the volume ratio of the etching solution in step five is HF solution: HNO3 solution: CH3CH(OH)COOH solution = 1:3:8, and the etching solution is first heated to 45°C to 55°C in a water bath, and then the dried high-temperature titanium alloy sample is placed in the etching solution for 10s to 20s to promote the movement of the etching solution molecules by heating the etching solution, so that the corrosion reaction is easier and more fully carried out.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] 1. The present invention uses a CrO3 aqueous solution containing AlO powder as a polishing liquid in rough polishing, which helps to quickly remove large scratches on the surface of the high-temperature titanium alloy sample. In combination with using a CrO3 aqueous solution containing Cr2O3 as a polishing liquid during fine polishing, it helps to quickly remove fine scratches on the surface of the high-temperature titanium alloy sample, thereby quickly removing scratches on the sample surface to achieve a mirror-bright scratch-free state, greatly improving the efficiency of preparing metallographic samples of high-temperature titanium alloys, and combining with subsequent etching processes to clearly and quickly etch out the microstructure of the sample.
[0019] 2. The present invention further ensures the polishing effect of each process by limiting the particle size of the polishing powder added to the polishing liquid and strictly controlling the composition ratio of the polishing liquid, thereby quickly removing scratches on the sample surface and improving the efficiency of preparing high-temperature titanium alloy metallographic samples.
[0020] 3. The present invention controls the heating temperature and erosion time of the corrosive liquid to avoid incomplete corrosion of the sample tissue due to too low temperature and short corrosion time, and excessive corrosion of the sample tissue due to too high temperature and long corrosion time, thereby affecting the analysis and judgment of the overall structure of the high-temperature titanium alloy.
[0021] 4. The sample preparation method of the present invention is simple, highly operable, and low in cost, and is suitable for the preparation of high-temperature titanium alloy metallographic samples.
[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the microstructure diagram of the Ti650 alloy metallographic sample prepared in Example 1 of the present invention.
[0024] Figure 2 This is the microstructure diagram of the Ti650 alloy metallographic sample prepared in Example 2 of the present invention.
[0025] Figure 3 This is the microstructure diagram of the Ti650 alloy metallographic sample prepared in Example 3 of the present invention.
[0026] Figure 4 This is the microstructure diagram of the Ti650 alloy metallographic sample prepared in Example 4 of the present invention.
[0027] Figure 5 This is the microstructure diagram of the Ti650 alloy metallographic sample prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0028] Example 1
[0029] This embodiment includes the following steps:
[0030] Step 1: Grind the Ti650 alloy sample using 150#, 500#, 1000#, and 2000# water-abrasive sandpaper in sequence, grinding each level of sandpaper for 3 minutes, and rotate the Ti650 alloy sample 90° each time the next level of sandpaper is replaced;
[0031] Step 2: Use a coarse canvas to roughly polish the Ti650 alloy sample ground in step 1 to a slightly bright state; the polishing liquid used for the rough polishing is a CrO3 aqueous solution containing AlO powder, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 6:100, and the CrO3 aqueous solution is mixed with water using CrO3 with a mass purity of not less than 99.0%, the ratio of the mass of AlO powder to the volume of the CrO3 aqueous solution is 10:100, the unit of mass is g, the unit of volume is mL, and the AlO powder is an aluminum oxide polishing micropowder with a particle size of 2.5 μm;
[0032] Step 3: Use fine silk cloth to fine-polish the Ti650 alloy sample after rough polishing in step 2 until it is mirror-bright and scratch-free; the polishing liquid used for the fine polishing is a CrO3 aqueous solution containing Cr2O3, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 6:100, and the mass purity of Cr2O3 is not less than 99.0%, the ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution is 8:100, the unit of mass is g, and the unit of volume is mL;
[0033] Step 4: Place the finely polished Ti650 alloy in an ultrasonic cleaner for 5 minutes and blow dry it with a hair dryer;
[0034] Step 5, placing the Ti650 alloy sample dried in step 4 into a corrosive solution for corrosion, then rinse with water, spray ethanol solution and use a hair dryer to dry, to obtain a Ti650 alloy metallographic sample, and place it under an optical microscope for metallographic structure observation; the raw materials of the corrosive solution include HF solution with a mass concentration of more than 40.0%, HNO3 solution with a mass concentration of 65.0% to 68.0%, and CH3CH(OH)COOH solution with a mass concentration of 85.0% to 90.0%, and the volume ratio of HF solution: HNO3 solution: CH3CH(OH)COOH solution is 1:3:10, and the corrosive solution is first heated to 60°C in a water bath, and then the dried Ti650 alloy sample is placed in it for etching for 10s.
[0035] Figure 1 The microstructure of the Ti650 alloy metallographic sample prepared in this embodiment is shown in FIG. Figure 1It can be seen that the microstructure of the Ti650 alloy metallographic sample is clearly displayed, and the primary α phase and the secondary α phase in the structure are fully displayed, which can accurately analyze and judge the overall structure of the Ti650 alloy. At the same time, the time for preparing the Ti650 alloy metallographic sample in this embodiment is shorter than that of the traditional method, and the sample preparation efficiency is greatly improved.
[0036] Example 2
[0037] This embodiment includes the following steps:
[0038] Step 1: Use 150#, 500#, 1000#, and 2000# water-abrasive sandpaper to grind the Ti650 alloy sample in sequence. Grind each level of sandpaper for 5 minutes, and rotate the Ti650 alloy sample 90° each time the next level of sandpaper is replaced.
[0039] Step 2: Use a coarse canvas to roughly polish the Ti650 alloy sample ground in step 1 to a slightly bright state; the polishing liquid used for the rough polishing is a CrO3 aqueous solution containing AlO powder, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 4:100, and the CrO3 aqueous solution is mixed with water using CrO3 with a mass purity of not less than 99.0%, the ratio of the mass of AlO powder to the volume of the CrO3 aqueous solution is 6:100, the unit of mass is g, the unit of volume is mL, and the AlO powder is an aluminum oxide polishing micropowder with a particle size of 1.5 μm;
[0040] Step 3: Use fine silk cloth to fine-polish the Ti650 alloy sample after rough polishing in step 2 until it is mirror-bright and scratch-free; the polishing liquid used for the fine polishing is a CrO3 aqueous solution containing Cr2O3, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 4:100, and the mass purity of Cr2O3 is not less than 99.0%, the ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution is 5:100, the unit of mass is g, and the unit of volume is mL;
[0041] Step 4: Place the Ti650 alloy sample finely polished in step 3 in an ultrasonic cleaner for oscillation cleaning for 5 minutes, and blow dry with a hair dryer;
[0042] Step 5, placing the Ti650 alloy sample dried in step 4 into a corrosive solution for corrosion, then rinse with water, spray ethanol solution and use a hair dryer to dry, to obtain a Ti650 alloy metallographic sample, and place it under an optical microscope for metallographic structure observation; the preparation raw materials of the corrosive solution include HF solution with a mass concentration of more than 40.0%, HNO3 solution with a mass concentration of 65.0% to 68.0%, and CH3CH(OH)COOH solution with a mass concentration of 85.0% to 90.0%, and the volume ratio of HF solution: HNO3 solution: CH3CH(OH)COOH solution is 1:3:8, and the corrosive solution is first heated to 55°C in a water bath, and then the dried Ti650 alloy sample is placed in it for etching for 20s.
[0043] Figure 2 The microstructure of the Ti650 alloy metallographic sample prepared in this embodiment is shown in FIG. Figure 2 It can be seen that the microstructure of the Ti650 alloy metallographic sample is clearly displayed, and the primary α phase and the secondary α phase in the structure are fully displayed, which can accurately analyze and judge the overall structure of the Ti650 alloy. At the same time, the time for preparing the Ti650 alloy metallographic sample in this embodiment is shorter than that of the traditional method, and the sample preparation efficiency is greatly improved.
[0044] Example 3
[0045] This embodiment includes the following steps:
[0046] Step 1: Grind the Ti650 alloy sample using 150#, 500#, 1000#, and 2000# water-abrasive sandpaper in sequence, grinding each level of sandpaper for 3 minutes, and rotate the Ti650 alloy sample 90° each time the next level of sandpaper is replaced;
[0047] Step 2: Use a coarse canvas to roughly polish the Ti650 alloy sample ground in step 1 to a slightly bright state; the polishing liquid used for the rough polishing is a CrO3 aqueous solution containing AlO powder, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 2:100, and the CrO3 aqueous solution is mixed with water using CrO3 with a mass purity of not less than 99.0%, the ratio of the mass of AlO powder to the volume of the CrO3 aqueous solution is 3:100, the unit of mass is g, the unit of volume is mL, and the AlO powder is an aluminum oxide polishing micropowder with a particle size of 1.5 μm;
[0048] Step 3: Use fine silk cloth to fine-polish the Ti650 alloy sample after rough polishing in step 2 until it is mirror-bright and scratch-free; the polishing liquid used for the fine polishing is a CrO3 aqueous solution containing Cr2O3, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 2:100, and the mass purity of Cr2O3 is not less than 99.0%, the ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution is 2:100, the unit of mass is g, and the unit of volume is mL;
[0049] Step 4: Place the Ti650 alloy sample finely polished in step 3 in an ultrasonic cleaner for oscillation cleaning for 5 minutes, and blow dry with a hair dryer;
[0050] Step 5, placing the Ti650 alloy sample dried in step 4 into a corrosive solution for corrosion, then rinse with water, spray ethanol solution and use a hair dryer to dry, obtain a Ti650 alloy metallographic sample, and place it under an optical microscope for metallographic structure observation; the preparation raw materials of the corrosive solution include HF solution with a mass concentration of more than 40.0%, HNO3 solution with a mass concentration of 65.0% to 68.0%, and CH3CH(OH)COOH solution with a mass concentration of 85.0% to 90.0%, and the volume ratio of HF solution: HNO3 solution: CH3CH(OH)COOH solution is 1:3:8, and the corrosive solution is first heated to 45°C in a water bath, and then the dried Ti650 alloy sample is placed in it for etching for 20s.
[0051] Figure 3 The microstructure of the Ti650 alloy metallographic sample prepared in this embodiment is shown in FIG. Figure 3 It can be seen that the microstructure of the Ti650 alloy metallographic sample is clearly displayed, and the primary α phase and the secondary α phase in the structure are fully displayed, which can accurately analyze and judge the overall structure of the Ti650 alloy. At the same time, the time for preparing the Ti650 alloy metallographic sample in this embodiment is shorter than that of the traditional method, and the sample preparation efficiency is greatly improved.
[0052] Example 4
[0053] This embodiment includes the following steps:
[0054] Step 1: Use 150#, 500#, 1000#, and 2000# water-abrasive sandpaper to grind the Ti650 alloy sample in sequence. Grind each level of sandpaper for 5 minutes, and rotate the Ti650 alloy sample 90° each time the next level of sandpaper is replaced.
[0055] Step 2: Use a coarse canvas to roughly polish the Ti650 alloy sample ground in step 1 to a slightly bright state; the polishing liquid used for the rough polishing is a CrO3 aqueous solution containing AlO powder, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 1:100, and the CrO3 aqueous solution is mixed with water using CrO3 with a mass purity of not less than 99.0%, the ratio of the mass of AlO powder to the volume of the CrO3 aqueous solution is 1:100, the unit of mass is g, the unit of volume is mL, and the AlO powder is an aluminum oxide polishing micropowder with a particle size of 1 μm;
[0056] Step 3: Use fine silk cloth to fine-polish the Ti650 alloy sample after rough polishing in step 2 until it is mirror-bright and scratch-free; the polishing liquid used for the fine polishing is a CrO3 aqueous solution containing Cr2O3, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 1:100, and the mass purity of Cr2O3 is not less than 99.0%, the ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution is 1:100, the unit of mass is g, and the unit of volume is mL;
[0057] Step 4: Place the Ti650 alloy sample finely polished in step 3 in an ultrasonic cleaner for oscillation cleaning for 5 minutes, and blow dry with a hair dryer;
[0058] Step 5, placing the Ti650 alloy sample dried in step 4 into a corrosive solution for corrosion, then rinse with water, spray ethanol solution and use a hair dryer to dry, to obtain a Ti650 alloy metallographic sample, and place it under an optical microscope for metallographic structure observation; the raw materials of the corrosive solution include HF solution with a mass concentration of more than 40.0%, HNO3 solution with a mass concentration of 65.0% to 68.0%, and CH3CH(OH)COOH solution with a mass concentration of 85.0% to 90.0%, and the volume ratio of HF solution: HNO3 solution: CH3CH(OH)COOH solution is 1:3:7, and the corrosive solution is first heated to 40°C in a water bath, and then the dried Ti650 alloy sample is placed in it for etching for 30s.
[0059] Figure 4 The microstructure of the Ti650 alloy metallographic sample prepared in this embodiment is shown in FIG. Figure 4 It can be seen that the microstructure of the Ti650 alloy metallographic sample is clearly displayed, and the primary α phase and the secondary α phase in the structure are fully displayed, which can accurately analyze and judge the overall structure of the Ti650 alloy. At the same time, the time for preparing the Ti650 alloy metallographic sample in this embodiment is shorter than that of the traditional method, and the sample preparation efficiency is greatly improved.
[0060] Comparative Example 1
[0061] This comparative example is a traditional metallographic sample preparation method, which includes the following steps:
[0062] Step 1: Use 150#, 500#, 1000#, and 2000# water-abrasive sandpaper to grind the Ti650 alloy sample in sequence. Grind each level of sandpaper for 5 minutes, and rotate the Ti650 alloy sample 90° each time the next level of sandpaper is replaced.
[0063] Step 2: polishing the Ti650 alloy sample ground in step 1 to a bright state; the polishing adopts diamond grinding paste;
[0064] Step 3, the Ti650 alloy sample polished in step 2 is placed in a corrosive solution for corrosion, then rinsed with water, sprayed with ethanol solution and dried with a hair dryer to obtain a Ti650 alloy metallographic specimen, which is placed under an optical microscope for metallographic structure observation; the raw materials for the corrosive solution include an HF solution with a mass concentration of more than 40.0%, an HNO3 solution with a mass concentration of 65.0% to 68.0%, and water, and the HF solution: HNO3 solution: water = 1:3:6 by volume, and the etching time is 35s.
[0065] Figure 5 The microstructure of the Ti650 alloy metallographic sample prepared in this comparative example is shown in FIG. Figure 5 It can be seen that the microstructure of the Ti650 alloy metallographic sample is not clear, and some primary α phases and most secondary α phases in the structure are not shown, which affects the accurate analysis and judgment of the overall structure of the Ti650 alloy. At the same time, the time for preparing the Ti650 alloy metallographic sample in this comparative example, especially the grinding and polishing time, is long, and the sample preparation efficiency is low.
[0066] By comparing Examples 1 to 4 of the present invention with Comparative Example 1, it can be seen that the sample preparation method of this embodiment greatly improves the efficiency of preparing metallographic samples of high-temperature titanium alloys, while clearly and quickly etching out the microstructure of the sample, ensuring the accuracy of analysis and judgment of the overall structure of the high-temperature titanium alloy.
[0067] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-temperature titanium alloy metallographic sample, characterized in that: The method comprises the following steps: Step 1: Grind the high-temperature titanium alloy sample using 150#, 500#, 1000#, and 2000# water-abrasive sandpaper in sequence, grinding each level of sandpaper for 3min to 5min, and rotate the high-temperature titanium alloy sample 90° each time the next level of sandpaper is replaced; Step 2, rough polishing the high-temperature titanium alloy sample ground in step 1 to a slightly bright state; the polishing liquid used for the rough polishing is a CrO3 aqueous solution containing AlO powder, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 1 to 6:100, the ratio of the mass of AlO powder to the volume of the CrO3 aqueous solution is 1 to 10:100, the unit of mass is g, and the unit of volume is mL; Step 3, fine-polishing the high-temperature titanium alloy sample after rough polishing in step 2 until it is mirror-bright and scratch-free; the polishing liquid used for the fine polishing is a CrO3 aqueous solution containing Cr2O3, wherein the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 1 to 6:100, and the ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution is 1 to 8:100, the unit of mass is g, and the unit of volume is mL; Step 4: Place the high-temperature titanium alloy sample finely polished in step 3 in an ultrasonic cleaning apparatus for oscillation cleaning for 3 to 5 minutes, and blow dry with a hair dryer; Step 5, placing the high-temperature titanium alloy sample dried in step 4 into a corrosive solution for corrosion, then rinse it with water, spray it with ethanol solution and use a hair dryer to dry it to obtain a high-temperature titanium alloy metallographic specimen, and place it under an optical microscope for metallographic structure observation; the raw materials for the preparation of the corrosive solution include HF solution with a mass concentration of more than 40.0%, HNO3 solution with a mass concentration of 65.0% to 68.0%, and CH3CH(OH)COOH solution with a mass concentration of 85.0% to 90.0%, and the volume ratio of HF solution: HNO3 solution: CH3CH(OH)COOH solution is 1:3:7 to 10. First, heat the corrosive solution in a water bath to 40°C to 60°C, and then put the dried high-temperature titanium alloy sample into it for etching for 10s to 30s.
2. A method for preparing a high temperature titanium alloy metallographic sample according to claim 1, characterized in that: The rough polishing in step 2 is performed using a coarse canvas, and the CrO3 aqueous solution is a mixture of CrO3 having a purity of not less than 99.0% and water.
3. The method for preparing a high-temperature titanium alloy metallographic sample according to claim 1, characterized in that: The AlO powder in step 2 is aluminum oxide polishing micropowder with a particle size of 1 μm to 2.5 μm.
4. The method for preparing a high-temperature titanium alloy metallographic sample according to claim 1, characterized in that: In step 2, the ratio of the mass of CrO3 in the CrO3 aqueous solution to the volume of water is 2-4:100, the AlO powder is alumina polishing micropowder with a particle size of 1 μm to 1.5 μm, and the ratio of the mass of AlO powder to the volume of the CrO3 aqueous solution is 3-6:
100. The unit of mass is g and the unit of volume is mL.
5. The method for preparing a high-temperature titanium alloy metallographic sample according to claim 1, characterized in that: In step 3, fine polishing is performed using fine silk cloth, and the CrO3 aqueous solution is a mixture of CrO3 with a purity of not less than 99.0% and water.
6. The method for preparing a high-temperature titanium alloy metallographic sample according to claim 1, characterized in that: The ratio of the mass of Cr2O3 to the volume of the CrO3 aqueous solution in step 3 is 2 to 5:100, the unit of mass is g, and the unit of volume is mL.
7. The method for preparing a high-temperature titanium alloy metallographic sample according to claim 1, characterized in that: The volume ratio of the etching solution in step 5 is HF solution: HNO3 solution: CH3CH(OH)COOH solution = 1:3:8, and the etching solution is first heated to 45°C to 55°C in a water bath, and then the dried high-temperature titanium alloy sample is placed in the etching solution for 10s to 20s.
Citation Information
Patent Citations
Metallographic corrosion method of high-strength beta titanium alloy
CN111579325A
Preparation method of high-temperature titanium alloy metallographic sample
CN115266269A
Metallographic display method of gallium arsenide polycrystal
CN117451713A
Cited By
Preparation method of metallographic small sample for observing phase change of high-temperature structure
CN120404270A
Method for in-situ observation of Ti alloy sample through high-temperature laser confocal microscope
CN122016738A